تحليل التركيب الكيميائي لبعض طحالب الماكرو من مناطق في الشاطئ السوري - قره علي أحمد; زينب اسمهان; عباس آصف (Latakia University Journal -Biological Sciences Series, 2017)
Two spaces of algae p. capillacea and Ulvafasciatawere collected fromJablah coast south of Lattakia coast. The results are revealing that all study samples contain a significant amount of hydrocarbons and carboxyl Acids and alcohols compounds. The hydrocarbons were more preferential in p. capillacea but kytons and alcohols were more preferential in Ulvafasciata, and aldehydes was preferential too in this space especially the compound 16- Heptadecanal . 1-(+)-ascorbic acid2- 6dihexadecanoate is the preferential in the two spaces as carboxylic acid derivatives, and cholesterol is the specific compound in alcohols of Ulvafasciata. تم دراسة التركيب الكيميائي لنوعين من الطحالب و هما p. capillacea و Ulvafasciataاللذين تم جمعهما من شاطئ مدينة جبلة جنوب اللاذقية ، لقد أشارت النتائج إلى أن العينات المدروسة تحتوي على تراكيز مهمة من الفحوم الهيدروجينية و الأحماض الكربوكسيلية و الكحولات حيث كانت الفحوم الهيدروجينية مميزة عند النوع p. capillacea بينما الكيتونات و الكحولات كانت مميزة عند النوع Ulvafasciata كذلك الأمر بالنسبة للأدهيدات أيضاً في هذا النوع وبصورة خاصة المركب 16- Heptadecanal . كان المركب 1-(+)-ascorbic acid2- 6dihexadecanoate المركب المميز في كلا النوعين من مشتقات الأحماض الكربوكسيلية و cholesterol كان المركب المميز من الكحولات في النوع Ulvafasciata.